SCULPTURAL EXPRESSIONS AND CULTURAL SYMBOLISM AT MADAN KAMDEV: A HISTORICAL STUDY - Pathak, Guptajit (International Journal of Research -GRANTHAALAYAH, 2021)
Early Kamarupa sculpture is a complex synthesis of socio-cultural worldviews, artistic imagination, and religious symbolism. The Madan Kamdev temple complex is a unique center of artistic exuberance among Assam's many archaeological monuments. It is especially well-known for its intricate carvings, angasikhara themes, floral portrayals, and sensuous representations. The location represents a mix of external aesthetic influences and local artistic vocabulary that influenced early medieval visual culture of Assam (Sharma,1998, p. 42). These sculptures, which vary in theme and design, show the ideological and symbolic frameworks that influenced the era's artistic activities. The empirical analysis of these sculptures shows that the Madan Kamdev complex functioned as a vibrant cultural center where various artistic traditions interacted in addition to being a place of worship. A vibrant aesthetic continuum spanning from the Pala period to later regional art traditions is suggested by the juxtaposition of architectural elements, iconographic patterns, and narrative panels (Barua, 2005, p. 119) In order to place Madan Kamdev into the larger context of Indian art history, this essay examines these sculptural forms using an empirical interpretive lens.